YB‐1 Transforms Human Mammary Epithelial Cells Through Chromatin Remodeling Leading to the Development of Basal‐Like Breast Cancer. (June 2014) - Davies, Alastair H.; Reipas, Kristen M.; Pambid, Mary Rose; Berns, Rachel; Stratford, Anna L.; Fotovati, Abbas; Firmino, Natalie; Astanehe, Arezoo; Hu, Kaiji; Maxwell, Christopher; Mills, Gordon B.; Dunn, Sandra E.
Abstract: There is growing evidence that cancer‐initiation could result from epigenetic changes. Y‐box binding protein‐1 (YB‐1) is a transcription/translation factor that promotes the formation of tumors in transgenic mice; however, the underlying molecular events are not understood. To explore this in a human model system, YB‐1 was expressed in mammary epithelial cells under the control of a tetracycline‐inducible promoter. The induction of YB‐1 promoted phenotypes associated with malignancy in three‐dimensional breast acini cultures. This was attributed to YB‐1 enhancing the expression and activity of the histone acetyltransferase p300 leading to chromatin remodeling. Specifically, this relaxation of chromatin allowed YB‐1 to bind to the BMI1 promoter. The induction of BMI1 engaged the Polycomb complex resulting in histone H2A ubiquitylation and repression of the CDKN2A locus. These events manifested functionally as enhanced self‐renewal capacity that occurred in a BMI1‐dependent manner. Conversely, p300 inhibition with anacardic acid prevented YB‐1 from binding to the BMI1 promoter and thereby subverted self‐renewal. Despite these early changes, full malignant transformation was not achieved until RSK2 became overexpressed concomitant with elevated human telomerase reverse transcriptase (hTERT) activity. The YB‐1/RSK2/hTERT expressing cells formed tumors in mice that were molecularly subtyped as basal‐like breast cancer. We conclude that YB‐1 cooperates with p300 to allow BMI1 to over‐ride p16 INK4a ‐mediated cell cycle arrest enabling self‐renewal and the development of aggressive breast tumors. Stem Cells 2014;32:1437–1450